The effect of chewing gum on dental plaque accumulation - Karami Nogourani M; Banihashemi M (Tehran University of Medical Sciences, 2010)
"nBackground and Aims: Studies show that sucrose containing chewing gums are cariogenic. The aim of this study was to evaluate the effect of two commercial chewing gums with and without sucrose on dental plaque accumulation compared with the control group. "nMaterials and Methods: In this clinical study, plaque accumulation during three 7-day periods (with two weeks interval) was recorded (Sillness & Loe Index) in a group of 23 volunteer male dental students who chewed in the first two periods sugar-free or sugar-containing chewing gums (Olips and Orbit, respectively) and in the last period did not chew any gum. Participants were asked to chew daily five gum sticks after meals for about twenty minutes. The data were statistically analyzed using Repeated Measure ANOVA and paired-T test. "nResults: The results showed that chewing any gum even sucrose-containing gum decreased the level of dental plaque accumulation (P<0.001). However, the decreasing effect of sugar-free gums was significantly higher (P<0.001). "nConclusion: Although sugar free gum was more effective than sugar containing gum on reducing dental plaque accumulation, chewing even sugar containing gums could decrease the level of dental plaque.